Subsistence and semi-subsistence farming in selected EU new member states - Sophia Davidova; Lena Fredriksson; Alastair Bailey (University of Kent, School of Economics, 2009)
Factor and cluster analysis are used to analyse the attitudes and perceptions of agricultural households in five EU New Member States towards farming, commercialisation, and barriers to and drivers for an increased integration in agricultural markets. The contribution of unsold output to the total household income is valued. A stepwise linear regression is employed to detect important variables explaining the degree of agricultural market integration of farm households. The analysis indicates that subsistence farming is of utmost importance for the rural poor, and particularly in Bulgaria and Romania. The proportion of consumption from own production, manual cultivation techniques and distance to an urban centre negatively affect output sales. Rural development policies targeted at rural physical and market infrastructure might relieve some of these constraints.
Keywords: Q12; Q13; O18; 330; agricultural households; subsistence; commercialisation; incomes; cluster analysis; stepwise regression; Landwirtschaftlicher Kleinbetrieb; Agrarproduktion; Kommerzialisierung; Subsistenzwirtschaft; Haushaltseinkommen; EU-Staaten (Osteuropa)